1999
DOI: 10.1080/00224549909598383
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Waitresses' Touch on Alcohol Consumption in Dyads

Abstract: A total of 96 men and 48 women participated in a study on the effect of touch in the natural setting of public taverns in the United States. Participants in the same-gender (men-men) or mixed-gender dyads were either touched or not touched by waitress confederates. Regardless of dyad type, participants who were touched consumed more alcohol than participants who were not touched. Men in the mixed-gender dyads consumed more alcohol when the women was touched. Same-gender (men-men) dyads aggregately consumed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Now, in the part of our experiment in which customers had to judge a seller, this desire to create affiliation and rapport could have been perceived as professional competence, because this desire is perceived as an important quality for a seller to posses if he wishes to improve his sales performance. With some nonverbal behavior like tactile contact, it has been found that a sales clerk or restaurant employee giving a slight touch to a customer, is associated with a higher buying rate, a greater amount of money spent, and larger tips given to an employee (Gué guen and Jacob, 2006;Hornik, 1992a;Kaufman and Mahoney, 1999;Smith et al, 1982). Concomitantly, the professional qualities of the seller or the restaurant employee were evaluated more positively (Crusco and Wetzel, 1984;Hornik, 1992b;Stephen and Zweigenhaft, 1986;Wycoff and Holley, 1990).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Now, in the part of our experiment in which customers had to judge a seller, this desire to create affiliation and rapport could have been perceived as professional competence, because this desire is perceived as an important quality for a seller to posses if he wishes to improve his sales performance. With some nonverbal behavior like tactile contact, it has been found that a sales clerk or restaurant employee giving a slight touch to a customer, is associated with a higher buying rate, a greater amount of money spent, and larger tips given to an employee (Gué guen and Jacob, 2006;Hornik, 1992a;Kaufman and Mahoney, 1999;Smith et al, 1982). Concomitantly, the professional qualities of the seller or the restaurant employee were evaluated more positively (Crusco and Wetzel, 1984;Hornik, 1992b;Stephen and Zweigenhaft, 1986;Wycoff and Holley, 1990).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have found that the tactile contact of a patron by a server in a restaurant or bar increases tipping (Crusco and Wetzel, 1984;Stephen and Zweigenhaft, 1986;Hornik, 1992b;Lynn et al, 1998;Ebesu Hubbard et al, 2003;Gué guen and Jacob, 2005). Touching potential customers can also lead to an increase in product sales rates, or a greater amount of money spent Gué guen and Jacob, 2006;Hornik, 1992a;Kaufman and Mahoney, 1999;Smith et al, 1982). Further studies found that the professional qualities of the seller or the restaurant employee were evaluated more positively (Crusco and Wetzel, 1984;Hornik, 1992b;Stephen and Zweigenhaft, 1986;Wycoff and Holley, 1990;Erceau and Gué guen, 2007).…”
Section: Interpersonal Bonds In Employee-customer Relationshipsmentioning
confidence: 96%
“…Then it could be interesting to evaluated the effect of touch in a bar to generalize the effect of tactile contact on tipping. Kaufman and Mahoney (1999) have found that men and women of public tavern in the United States consumed more alcohol when touched by a waitress. Despite the fact that tips was not the dependant variable in this experiment, it seems that the customer behavior was affected by tactile contact in this context.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, Stephen and Zweigenhaft [109] replicated this basic phenomenon, showing that touching female diners led to a 4% increase in the tips received, as compared to touching male diners, or not touching anyone at all [see also [110]. Meanwhile, researchers have also demonstrated that drinkers tend to consume more food if touched by a waitress [111]. In one study, those people drinking in pairs consumed significantly more after having been touched by the waitress; while in another study, diners were more likely to agree to a suggestion made by a waiter or a waitress after tactile contact (around 60% of times they were touched, they ordered the dish that had been suggested to them; [112]).…”
Section: Social Touch In the Restaurant: The Midas Touchmentioning
confidence: 68%